High school grammar and writing teaching in Quebec: Results of a descriptive research - Chartrand, Suzanne-G.; Lord, Marie-Andrée (Swiss Journal of Educational Research, 2018)
To address the lack of data on the teaching of French in Quebec high schools, the research ITF (Inventory of teaching of French in Quebec high schools) conducted a survey among a group of teachers of French and students from the fourth and fifth secondary grades, and analysed ten sequences of five to eight courses in French. Firstly, the researchers found that the situation was similar to the one observed by the research conducted by the Council of the French language in 1985 and, secondly, that neither the requirements of the curriculum nor the research in French teaching seem to have greatly influenced the teaching practices.